Physico-chemical and organoleptic properties of palm oil and it's comparison with other oils regarding their utility in preparation of food products: PHYSICO-CHEMICAL AND ORGANOLEPTIC PROPERTIES OF PALM OIL AND OTHER OILS - MAMTA KUMARI; RITU P DUBEY (Journal of Oilseeds Research, 2019)
Palmoil is the most widely used vegetable oil in the world. It is widely used by food and non-food manufacturers because of its functional benefits, versatility and availability. The consumption of palm oil is increasing as it is one of the cheapest forms of vegetable oil. It is rich in natural chemical compounds important for health and nutrition. The present study was carried out to prepare and assess the physico-chemical qualities of food products formulated by palm oil and other commonly used vegetable oils. Properties of palm oil with other vegetable oils (soybean oil and sunflower oil) were compared by preparing two food products namely Namak Para and Sev and they were evaluated for sensory evaluation. The chemical properties of the oils were analysed by calculating the acid value, peroxide value, specific gravity, percentage of oil absorption and beta-carotene. The cost of developed products was also calculated. The results indicated that organoleptic scores of Namak Para and Sev prepared using palm oil were significantly higher than the products prepared in other oils. Therefore, palm oil is recommended for cooking purposes because of its comparatively better sensory, physico-chemical and nutritional qualities.